Thomas Sigaud, Mobilités résidentielles et professionnelles des salariés en France : entreprises, marchés et territoires, une articulation en tension - Thomas Sigaud (Revue de la Régulation)
Be it a human resources management device or a solution to labor market dysfunctions, employee residential mobility is the focus of a range of injunctions that ignore dwelling conceptions based on stability and mooring in places. This thesis aims to study the way individuals articulate their residential and professional mobilities by crossing quantitative and qualitative research. Residential mobilities in France are not higher now than in the 1960’s, and are coincident with upward as well as downward social mobilities. The issue is raised to study the social logics of the triggering and the resolving of mobility. Relocation is a human resources management device that has to be confronted to the social logics of territorial moorings. Relocated employees have to “enter territories”. This “entering” has be studied through the market intermediation activity of relocation service providers. A relocation market slowly emerges, and its atypical competition dynamics has a strong influence on how employees conciliate private life and work life.